Six-Minute Walk Test in Children With Cerebral Palsy Gross Motor Function Classification System Levels I and II: Reproducibility, Validity, and Training Effects - Nsenga Leunkeu, Angeline; Shephard, Roy J.; Ahmaidi, Said (Archives of physical medicine and rehabilitation, 2012)
Nsenga Leunkeu A, Shephard RJ, Ahmaidi S. Six-minute walk test in children with cerebral palsy Gross Motor Function Classification System levels I and II: reproducibility, validity, and training effects. To assess the reproducibility and validity of the 6-minute walk test (6MWT) with gas collection, and to evaluate effectiveness of a walking program in children with cerebral palsy (CP). Assessment and controlled training study. Rehabilitation service. Children/adolescents with CP (N=24; 12 boys, 12 girls; mean age, 14.2±2.0y, Gross Motor Function Classification System levels I and II). After a cycle-ergometer stress test and the 6MWT, subjects were assigned to training (n=12, 40min of moderate walking exercise 3 times per week for 8wk) or a matched control group (n=12). Peak oxygen consumption (V̇o2peak), peak ventilation, peak heart rate, and 6MWT distance. Test-retest correlations for the 6MWT were good (V̇o2peak: r=.90, P<.001, intraclass correlation coefficient [ICC]=.85; peak ventilation: r=.88, P<.001, ICC=.83; peak heart rate: r=.86, P<.001, ICC=.82; distance walked: r=.87, P=.007, ICC=.80). Mean scores for the 6MWT also closely matched corresponding cycle-ergometer data. Significant improvements in 6MWT V̇o2peak, peak ventilation, and peak heart rate were found after 8 weeks of training (P<.05). The 6MWT appears reproducible and valid relative to cycle-ergometer assessments of cardiorespiratory responses, and offers a simple method of clinical assessment. An 8-week moderate walking program improves the cardiopulmonary fitness of children with CP, as measured by 6MWT.